2015
DOI: 10.1155/2015/398642
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem and Progenitor Cells Can Be Enriched by Implanting Biomaterial into Spatium Intermusculare

Abstract: Hematopoietic stem and progenitor cells (HSPCs) have been used successfully to treat patients with cancer and disorders of the blood and immune systems. In this study, we tried to enrich HSPCs by implanting biomaterials into the spatium intermusculare of mice hind limbs. Gelatine sponges were implanted into the spatium intermusculare of mice and then retrieved after 12 days. The presence of HSPCs in the migrating cells (MCs) was detected by phenotypically probing with CD34+Sca-1+ and functionally confirming th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…As early as 1995, Narotam et al ( 25 ) found that gelatin sponges promoted fibroblast activity, accelerated the dural regeneration, and had satisfactory clinical effects on preventing spinal nerve root adhesion. Tong et al ( 26 ) demonstrated that hematopoietic stem and progenitor cells (HSPCs) could be enriched by implanting biomaterials into spatium intermusculare, which could be beneficial for patients’ recovery. However, Buyuktepe et al ( 27 ) reported a case of acute hydrocephalus due to application of gelatin sponges, and it was revealed that CSF flow was immediately restored after removing this material, in which an additional ventriculostomy was performed.…”
Section: Discussionmentioning
confidence: 99%
“…As early as 1995, Narotam et al ( 25 ) found that gelatin sponges promoted fibroblast activity, accelerated the dural regeneration, and had satisfactory clinical effects on preventing spinal nerve root adhesion. Tong et al ( 26 ) demonstrated that hematopoietic stem and progenitor cells (HSPCs) could be enriched by implanting biomaterials into spatium intermusculare, which could be beneficial for patients’ recovery. However, Buyuktepe et al ( 27 ) reported a case of acute hydrocephalus due to application of gelatin sponges, and it was revealed that CSF flow was immediately restored after removing this material, in which an additional ventriculostomy was performed.…”
Section: Discussionmentioning
confidence: 99%